Abnormal persistence of embryonic blood supply of liver: anatomist's delight, surgeon's nightmare - Yaseen, Sabah; Wadhwa, Surbhi; Jeelani, Kahkashan; Mahajan, Anita; Mishra, Sabita (Acta Medica, 2019)
The high incidence of hepato-biliary vascular anatomy variations necessitates its evaluation prior to performing liver transplantation, hepatobiliary, pancreatic, gastric and oesophageal surgeries. We report a unique case of persistence of embryonic arteries of the liver, wherein, the liver was supplied by five vessels. In addition to the usual right and left hepatic arteries from the hepatic artery proper, the liver received two accessory right hepatic arteries, one from the gastroduodenal artery, while another arising from superior mesenteric artery and an accessory left hepatic artery, from the left gastric artery. The origin of gastroduodenal artery was found to be unusually high and its abnormal anterior course over the common bile duct further added complexity to the hepatobiliary anatomy. The presence of these aberrant and accessory arteries predisposes to inadvertent injury leading to patient morbidity and sometimes mortality.
Keywords: jaterní oběh; transplantace jater; Liver; Aged, 80 and over; arteriae mesentericae; Hepatic Artery; játra; ženské pohlaví; Mesenteric Arteries; Humans; senioři nad 80 let; Female; arteria hepatica; Liver Transplantation; Liver Circulation; lidé